Ghrelin Ameliorates Nicotine induced Renal Damage in Balb/c mice: RCT - Aqsa Jabeen, Asma Jabeen, Mubashar Nazar, Sana Razzaq, Zara Shaukat (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Kidneys are the major organs responsible for elimination of toxic metabolites from the body. Aim: To determine role of ghrelin in mitigating nicotine induced renal damage in Balb/c mice by assessing serum creatinine levels, renal tissue MDA levels and renal tubular histological changes. Methodology: It was a Randomized Control Trial. Healthy male BALB/c mice (n=27) through non probability convenience sampling were taken from NIH Islamabad and sorted into 3 groups (nine each). Group I was labeled as control group and given intraperitoneal normal saline for 29 days. Group II was labeled as nicotine group and received intraperitoneal nicotine for 29 days. Group III was labeled as ghrelin + nicotine and received intraperitoneal ghrelin on alternate days and nicotine daily for 29 days. On 30th day intracardiac sampling was done for estimation of serum creatinine. After intra cardiac sampling dissection was done to obtain renal tissue sample for lipid peroxidation and histological analysis. Data was evaluated by using SPSS version 23. One way ANOVA and post hoc tukey’s test were applied. Results: In group 2, nicotine administration markedly elevated serum creatinine and tissue MDA levels whereas ghrelin administration along with nicotine in group 3 restored serum creatinine and tissue MDA levels back to normal. Renal tubular changes caused by nicotine in group-2 are also mitigated by ghrelin and nicotine administration in group-3. Practical Implication: Ghrelin a newly discovered peptide has shown to have anti-oxidant properties and nephro-protective effect thus has potential to reduce renal damage. It can restored creatinine levels thus minimizes renal damage. Conclusion: It was concluded that ghrelin protects kidneys against nicotine induced renal damage by restoring serum creatinine, lipid peroxidation marker and histological changes. Keywords: Ghrelin, Lipid Peroxidation, Nicotine, Nephro-Protection, Anti-Oxidant and MDA.